Improvement of the pad wear shape in fixed abrasive chemical-mechanical polishing for manufacturing optical components - Nguyen, N. Y. (2018)
Fixed abrasive chemical mechanical polishing has some advantages in generating planarity surfaces of optical components. The surface after polishing has better uniformity, and the material removal rate is much more than the traditional chemical mechanical polishing. The pad wear shape has a significant effect on the uniformity of the surface in the chemical mechanical polishing process. The shape of the pad after wear is almost concave, and it has been challenging to create a flat surface. Therefore, there is a requirement for creating a better pad shape. The better the pad shape is, the more uniform the surface is. Kinematic analysis has been done to investigate the effect of the conditioning process on the pad shape. Some proposals are presented to create a better pad shape. In this paper, kinematic aspects of effects of the conditioner speed and the pad speed on the pad shape were investigated. In addition, a new model, including new designs of the conditioner and pad, is proposed. The conditioner in the new model is static instead of oscillation. The new model generates a better uniformity of the pad shape compared to the old model. The result was validated by an algorithm which was validated by the experiments reported in our previous paper.